URGENSI KEBIJAKAN DAN INOVASI PAI DI LEMBAGA PENDIDIKAN - Dini Apriliani Khairunissa Gurnadi (LPPM STAI Muhammadiyah Probolinggo, 2026)
Abstract: According to Law no. 20 of 2003 concerning the National Education System, education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential. The foundation of education referring to Pancasila and the 1945 Constitution must remain rooted in Indonesian national religious and cultural values. Therefore, it is very important to pay attention to educational policies and innovations so that education runs directly in accordance with current conditions. However, it is also important to note that educational innovation must instill Islamic values so that it is in accordance with PMA Republic of Indonesia No. 13 of 2013 concerning Islamic Religious Education states that the implementation of education must instill in students the need to have faith and devotion to Allah SWT. However, great attention from the state alone is not enough, because practitioners and academics must strive hard to carry out continuous innovation in managing and developing education. This educational innovation must be based on educational goals to improve the quality of education, which will ultimately make the life of the nation intelligent and form competitive and dignified people.